MYDEGS supervisor selection system: Towards promoting expertise of theses supervisors in Malaysia higher education institutions to global audience (Global Business Management Review (GBMR), 2023)
Applicants for post-graduate research studies find it difficult to identify potential supervisors before applying for admission. This is because there is no single point at which they can browse for that information. In order to address this practical gap in post graduate education and communication management, this study proposed a one-stop-centre called MYDEGS Supervisor Selection System, as a platform for applicants to identify suitable supervisors who meet the criteria in terms of research field and expertise they desire before applying for admission into the Malaysian Higher Education institution. This project was initiated by the Graduate Dean's Council of Malaysia (MYDEGS). The data gathering for system and data requirements were performed by two researchers, who were also members of MYDEGS, during several MYDEGS meetings. Twenty public universities were involved in supplying the data of 2000 experts in the country. The completed system was tested by potential users from all participating universities. It was found that the system was fully functional and its objective of assisting prospective Ph.D candidates in identifying potential supervisors was achieved. Emerging issues and the way forward are discussed.